‘An experience of meaning’: A 20-year prospective analysis of delusional realities in schizophrenia and affective psychoses - Rosen, Cherise; Harrow, Martin; Humpston, Clara; Tong, Liping; Jobe, Thomas H.; Harrow, Helen (Frontiers in Psychiatry, 2022)
Delusions are transdiagnostic and heterogeneous phenomena that exist along a continuum with varying intensity, stability, and dimensional attributes where the boundaries between everyday beliefs and delusional beliefs can be clearly demarcated, fuzzy, or indistinguishable. This highlights the difficulty in defining delusional realities. All individuals in the current study were evaluated at index and at least one of six follow-ups over 20 years in the Chicago Longitudinal Study. We assessed 16 distinct delusions categorized as thought or thematic delusions. We also examined the probability of recurrence and the relationships between delusions and hallucinations, depression, anxiety, and negative symptoms. The sample consisted of 262 individuals with schizophrenia versus affective psychosis. Thought delusions were significantly different between groups at all follow-ups except the 20-year timepoint. Thematic delusions were more common than thought delusions and showed a significant decreasing pattern. Referential, persecutory, and thought dissemination delusions showed the highest probability of recurrence. Hallucinations were the strongest indicator for thought, thematic, and overall delusions. The formation and maintenance of delusions were conceptualized as a multimodal construct consisting of sensory, perceptual, emotional, social, and somatic embodiment of an “experience of meaning”, and delusional content varied over time. Given the significant associations between delusions and hallucinations, future participatory research is needed to better define and align subjective and objective research objectives. Our research also points to the need for future clinical interventions that specifically evaluate and target the coexistence and entanglement of delusions and hallucinations.